BLOCKYLAND: A Cellular Automata-Based Game to Enhance Logical Thinking. (August 2016) - Dhatsuwan, Apinya; Precharattana, Monamorn
Background: BLOCKYLAND is acity building game based on the concept ofcellular automata (CA), andurban cellular automata . Thegame hasCA-like processes that invert the role of players from passive observers in otherCA applications to active thinkers. The processes challenge players to applylogical thinking anddecision making from the perspective ofserious games . The players' mission is to build a city by applying the providedCA rules. Two types ofCA rules are provided: 1) The logical rule, whereby players apply to build the city according to the preset conditions, and 2) The optional rule, whereby they may apply to upgrade an existing building for an extra score. Aim: This article aims to present the design and development ofCA-based game, BLOCKYLAND and describe its effectiveness as aninstructional tool to enhancelogical thinking . Results: Results from the mixed-method pilot study show thatBLOCKYLAND enhanced players'logical thinking after the gameplay. Additionally, from the extensivedebriefing following the game, participants stated that the game aided them with transforming their game experiences into learning experiences and relating the logical thinking practice into real-life application. Results: Conclusion. As a combination of logical thinking practices and a serious game, BLOCKYLAND has several implications for educational stakeholders; both theoretical and practical.